Differences of SiHa (Human Cancer of Cervix) and BMG‐1 (Brain Glioma) Cell Lines as 2D and 3D Cultures. Issue 2 (25th October 2013) - Ravi, Maddaly; Sah, Sunil; Bhammar, Rajesh
Abstract Cell cultures have seen much progress in the numbers available cell lines, their applications and culture techniques. Three dimensional cultures and co‐cultures are examples of strategies that bring in vitro conditions closer to natural in vivo systems. We describe here, the formation of cell aggregates in three‐dimensional conditions for the cell lines SiHa and BMG‐1 utilizing agarose hydrogels. The optimal conditions for best aggregate formation were identified and the culture phases for the cell lines as monolayers and as aggregates were compared. Differences in protein profiles, susceptibility to a genotoxic drug and the antigenic properties of the protein extracts of the two cell lines, as can be induced by their aggregate formation were studied. The results from the four approaches indicate the usefulness of culturing cells as aggregates. Such systems using simple material and methods offer us an efficient way of utilizing cell lines for a variety of applications. J. Cell. Physiol. 229: 127–131, 2014. © 2013 Wiley Periodicals, Inc.